The Thoughts of Economic Growth Theories of Classical Muslim Scholars, A Contribution - Tubagus Thresna Irijanto; Mohd. Azlan Shah; Abdul Ghafar Ismail (TRIKONOMIKA, 2013)
This paper attempts to view at the development of Islamic thought in the study of economics and economic growth. In particular, it attempts to explore the similarities and differences between Islamic ideas about economics and to construct economic growth thought and how it used to bridge the gap. The analysis starts from Muslim thought Ibn Khaldun, Al-Ghazali and Ibn Taymiyyah. In addition, the study looked at how the views of classical Islamic scholars had entered into the idea of economic growth. Suggestions will be made on how the gap can be bridged or made closer to contemporary economic thought and economic direction of the country’s future.